Intraspecific differences in spring leaf phenology in relation to tree size in temperate deciduous trees. (26th February 2019) - Osada, Noriyuki; Hiura, Tsutom
Abstract: Spring leaf phenology strongly influences plant productivity in temperate deciduous forests. Many studies have detected earlier budburst and leaf maturation in smaller trees within species, and have discussed the adaptive significance of increasing carbon gain before canopy closure in small trees. However, some previous studies have found the opposite pattern, and the physiological and environmental bases for this discrepancy are incompletely understood. We investigated the spring leaf phenology of 11 deciduous species in a cool-temperate forest in Japan for 2 years with different amounts of snowfall, and also gathered data on the day of budburst from multiple studies to assess whether and how the timing of budburst is related to tree size, phylogeny, temperature and annual snowfall of study sites. We found that differences in the timing of budburst and leaf maturation between saplings (<1 m height) and short trees (1–10 m height) are larger than those between short trees and tall trees (>10 m height), resulting in non-linear relationships between timing and height in most species. Cumulative degree-days to the day of budburst were smaller in saplings than in tall trees, probably because saplings are selected to outcompete the other individuals/species to become established. Moreover, phylogenetic relatedness did not explain the difference in spring leaf phenology between saplings and tall trees in the literature survey. In addition, our literature survey showed that budburst occurred earlier in saplings of most species in sites with less snowfall, whereas budburst occurred earlier in tall trees at sites with heavy snowfall. These results suggest that the opposite patterns found in some studies may be due to (i) differences in the target size, as saplings show larger phenological discrepancies than short and tall trees, and (ii) the microclimate experienced by the tree, as sites with heavy snow show delayed sapling phenology.